Genome‐wide chromatin occupancy of BRDT and gene expression analysis suggest transcriptional partners and specific epigenetic landscapes that regulate gene expression during spermatogenesis. Issue 2 (20th January 2021) - Her, Yoon Ra; Wang, Li; Chepelev, Iouri; Manterola, Marcia; Berkovits, Binyamin; Cui, Kairong; Zhao, Keji; Wolgemuth, Debra J.
Abstract: BRDT, a member of the BET family of double bromodomain‐containing proteins, is essential for spermatogenesis in the mouse and has been postulated to be a key regulator of transcription in meiotic and post‐meiotic cells. To understand the function of BRDT in these processes, we first characterized the genome‐wide distribution of the BRDT binding sites, in particular within gene units, by ChIP‐Seq analysis of enriched fractions of pachytene spermatocytes and round spermatids. In both cell types, BRDT binding sites were mainly located in promoters, first exons, and introns of genes. BRDT binding sites in promoters overlapped with several histone modifications and histone variants associated with active transcription, and were enriched for consensus sequences for specific transcription factors, including MYB, RFX, ETS, and ELF1 in pachytene spermatocytes, and JunD, c‐Jun, CRE, and RFX in round spermatids. Subsequent integration of the ChIP‐seq data with available transcriptome data revealed that stage‐specific gene expression programs are associated with BRDT binding to their gene promoters, with most of the BDRT‐bound genes being upregulated. Gene Ontology analysis further identified unique sets of genes enriched in diverse biological processes essential for meiosis and spermiogenesis between the two cell types, suggesting distinct developmentally stage‐specific functions for BRDT. Taken together, our data suggest that BRDT cooperates with different transcription factors at distinctive chromatin regions within gene units to regulate diverse downstream target genes that function in male meiosis and spermiogenesis. Abstract : We identified and characterized that BRDT binds preferentially at highly transcribed genes that have known functions during spermatogenesis in pachytene spermatocytes and round spermatids. BRDT‐bound regions are enriched for consensus sequences for the transcription factors MYB, RFX, ETS, and ELF1 in PS, and JunD, c‐Jun, CRE, and RFX in RS.